Enhanced electrocatalytic hydrogen evolution with CoNiFe(Cr/V) based high entropy alloy electrodes - Tahir Nawaz; Shahbaz Ahmad; Wael Abuzaid; Faisal Mustafa; Waqas Ahmad; Sami El-Khatib; Mohamad Jawad Kaddoura; Abdul Hai Alami; Hussain Alawadhi; Mehmet Egilmez (APL Materials)
In this study, the electrocatalytic properties of single-phase face-centered cubic high entropy alloy electrodes with equiatomic compositions of CoNiFeCr, CoNiFeV, and CoNiFe(Cr/V) are explored for the hydrogen evolution reaction (HER) in 1M KOH and 0.5M H2SO4. Among these, the CoNiFe(Cr/V) High Entropy Alloy (HEA) electrodes exhibited superior performance, achieving overpotentials of 277 and 45 mV (vs reference hydrogen electrode) at 10 mA/cm2 in alkaline and acidic media, respectively, surpassing their counterparts and approaching the efficiency of commercial Raney-Ni and Pt/C catalysts. Long-term stability tests, including steady state chronoamperometry and potentiodynamic cyclic voltammetry, revealed remarkable corrosion resistance in both environments. The catalytic activity was significantly enhanced by the inclusion of Cr and V. These oxyphilic elements, with their larger atomic radii, induce a heterogeneous surface charge distribution that enhances the electrocatalytic performance of the CoNiFe(Cr/V) HEA. This work highlights a promising candidate for HER applications and sets the stage for a broader exploration of high entropy alloys in advanced catalytic systems.